The Factors of Affecting The Intention of Merchandise In Flight - Helda Wahyurizki; Vina Pebianti; Mitsalina Tantri (Journal of Business and Behavioural Entrepreneurship, 2023)
This study aims to determine the effects of attitude, brands, social influence and satisfaction on purchase intentions of merchandise in flight to air transportation service users both domestically and abroad. This research used accidental sampling technique which was conducted on 201 samples from users of domestic or foreign air transportation services in 2019. The method was a questionnaire and an interview. By using SEM Amos 21 statistical tools. The results showed that all variables used in this study were attitudes, brands, social influences and satisfaction had a significant and positive influence on purchase intention variables. This shows that the presence of internal and external factors of a customer will also affect the customer's purchase intention for a merchandise.